Will the Circle Be Unbroken: The Making of a Landmark Album, 50th Anniversary - McEuen, John (Rowman & Littlefield Publishers, 2022)
The 1971 collaboration of legendary Nashville bluegrass musicians and the Nitty Gritty Dirt Band, a Southern California country-rock-jug group, was the genesis of Will the Circle Be Unbroken, which Rolling Stone magazine would declare "the most important album to come out of Nashville." In this definitive, beautifully illustrated book, McEuen gives an inside look at the making of a landmark album, covering each of its thirty-eight songs and sharing previously unseen photographs taken by the author and his brother Bill McEuen, who produced the recording. The story of the album begins after the Nitty Gritty Dirt Band's cover of "Mr. Bojangles" became a surprise hit, when McEuen invited Earl Scruggs to join the band on a new project. Scruggs said yes—as did Doc Watson, Merle Travis, Jimmy Martin, Vassar Clements, Roy Acuff, Mother Maybelle Carter, and other country stars. For six days in the summer of 1971, the musicians sat in a circle facing one another, recording country and bluegrass standards in East Nashville's Woodland Studios. Out of that magical collaboration came one of the most iconic albums in American history, one that melded musical worlds, bridged generations, and captured the essence of Americana. Now, after fifty years, John McEuen invites readers to join him in the circle, hear the stories, and listen to the music.